Cardiac Myxomas - Symptomology, Investigations and Surgical Treatment - Single Centre Experience of Fifteen Years at Grant Medical College, Mumbai, Maharashtra - Nagre, Suraj Wasudeo; Bhosle, Krishnarao N (Journal of Cardiovascular Medicine and Cardiology, 2018)
Introduction: The aim of study is to describe the clinical symptoms, investigation findings and surgical treatment of cardiac myxomas. Method: From May 2002 to May 2017, 50 patients of primary or recurrent intracardiac myxoma underwent surgical excision at our institute. Their age ranged from 25 years to 55 years. Out of which 20 males and 30 females. Commonest presenting symptoms are dyspnea and palpitation. 35 Left atrial, 13 Right atrial, one right ventricular and one left ventricular myxoma. The diagnosis was done by transthoracic and transesophageal echocardiography. The complete wide excision with margin of 3-5 mm normal surrounding tissue was the main principle of surgery. Right atriotomy, right ventricular and left ventricular surgical approach was used. Post-operative echocardiogram was done in all patients before discharge. Maximal follow-up of five years and minimum follow-up of 6 months was done after surgery. Results: No mortality. On followup after five years of surgery, all patients were in NYHA class 1 and their echocardiography showed good ventricular function with normal pulmonary artery pressure with patch in situ. One of patient right atrial myxoma developed left atrial myxoma after five years of first surgery that also excised. Conclusion: We recommend right atriotomy approach for both right and left atrial myxomas. Right ventricle approach for right ventricular myxoma and left ventricular for left ventricular myxoma. Biatrial approach in large and unusually located left atrial myxoma. To prevent recurrence the surgical excision must include a substantial portion of normal surrounding tissue near the base of implantation. With proper surgical technique no mortality and recurrence with complete recovery.